Pengaruh Kemandirian Terhadap Prestasi Belajar (Wiyatamandala, 2021)
ABSTRACTThe Effect of Self-Reliance on Learning Achievement. This study aims to determine whether there is a positive and significant influence between the attitude of independence on student achievement in Pancasila and Citizenship Education Subjects. The research method used in this research is the quantitative approach correlation method, which looks at the influence of the variables studied, namely the influence of students' independent attitudes on learning achievement in Pancasila and Citizenship Education Subjects in Class X Marketing at SMK Sirajul Falah Parung. Through answers to questionnaires or questionnaires given to students who are the target subjects studied. The target population is1066 students, while the reachable population is 136 students. In sampling, the authors took samples using the Slovin formula, from 4 affordable population classes in order to obtain a sample of 101.  Keywords: Independence; Learning achievement.  ABSTRAKPenelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh yang positif dan signifikan antara  sikap  kemandirian  terhadap  prestasi belajar siswa  dalam Mata Pelajaran  Pendidikan Pancasila dan Kewarganegaraan. Metode penelitian yang digunakan dalam penelitian ini adalah metode korelasi pendekatan kuantitatif, yakni melihat pengaruh antara variabel yang diteliti yaitu Pengaruh Sikap Kemandirian Peserta Didik Terhadap Prestasi Belajar Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan Pada Kelas X Pemasaran SMK Sirajul Falah Parung. Melalui jawaban dari angket atau kuesioner yang diberikan kepada peserta didik yang menjadi target subjek yang diteliti. Populasi target 1066 peserta didik, sedangkan populasi terjangkau ada sebanyak 136 peserta didik. Dalam pengambilan sampel, penulis mengambil sampel dengan menggunakan rumus slovin,dari 4 kelas populasi terjangkau sehingga didapatkan Sampel sebanyak 101.Kata Kunci: Kemandirian; Prestasi belajar.